2018
DOI: 10.1021/acs.jpcb.8b08536
|View full text |Cite
|
Sign up to set email alerts
|

Renewable Hydride Donors for the Catalytic Reduction of CO2: A Thermodynamic and Kinetic Study

Abstract: Increasing atmospheric CO 2 concentration and dwindling fossil fuel supply necessitate the search for efficient methods for CO 2 conversion to fuels. Assorted studies have shown pyridine and its derivatives capable of (photo)electrochemically reducing CO 2 to methanol, and some mechanistic interpretations have been proposed. Here, we analyze the thermodynamic and kinetic aspects of the efficacy of pyridines as hydride-donating catalytic reagents that transfer hydrides via their dihydropyridinic form. We invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 78 publications
0
11
0
Order By: Relevance
“…pK a values are obtained by creating a linear fit between experimentally determined pK a values and the computed free energy difference . While it is common to estimate pK a values using an isodesmic approach or use a pre-determined free energy of solvated protons ( Alherz et al., 2018 ; Thapa and Schlegel, 2016 ), we argue that a linear fitting approach avoids any systematic errors in pK a predictions. Figure S3 shows the linear correlation described.…”
Section: Methodsmentioning
confidence: 90%
See 1 more Smart Citation
“…pK a values are obtained by creating a linear fit between experimentally determined pK a values and the computed free energy difference . While it is common to estimate pK a values using an isodesmic approach or use a pre-determined free energy of solvated protons ( Alherz et al., 2018 ; Thapa and Schlegel, 2016 ), we argue that a linear fitting approach avoids any systematic errors in pK a predictions. Figure S3 shows the linear correlation described.…”
Section: Methodsmentioning
confidence: 90%
“…Because imidazolium cations ImH + are aromatic, the reduction of ImH + to add an electron to the imidazolium π-system results in de-aromatization of the imidazolium ring. Prior studies have shown that aromatic hydrides exhibit a linear correlation between the first reduction potential of the oxidized hydride and the nucleophilicity of the hydride ( Alherz et al., 2018 ; Ilic et al., 2018 ). To verify this correlation for imidazolium salts, we measured E red for a family of imidazolium salts ( Figure S1 and Table S1 ) using normal pulse voltammetry (NPV).…”
Section: Resultsmentioning
confidence: 99%
“…The M06-2X-computed molecular orbitals were viewed using Avogadro. Reductional potential calculations were performed based on the approach developed by Tossell. , Electron densities were computed using atomic polar tensor population analysis. , …”
Section: Experimental and Computational Detailsmentioning
confidence: 99%
“…Reductional potential calculations were performed based on the approach developed by Tossell. 56,57 Electron densities were computed using atomic polar tensor population analysis. 58,59 The photophysical properties of λ max , its corresponding molar absorptivity (ε max ), and changes in the electron occupation of active orbitals upon photoexcitation of chromophores were computed using TD-DFT at the M06-2X/6-311++g(d,p)/SMD-acetonitrile level of theory with geometries optimized with DFT at the M06-2X/6-31+g(d,p)/SMD-acetonitrile level of theory.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…Therefore, organomolecules that undergo multi-electron CO2RR are limited. [25][26][27][28][29][30][31][32] Successful examples are reactions using a combination of frustrated Lewis pairs and metalloid hydride species (B-H or Si-H) (Fig. 1C).…”
mentioning
confidence: 99%